Is the a the question or are you adding it
1/2 because the baker has 4 cups of strawberries after they make the cheesecake and the 4 cups divided between the 8 batches would equal 1/2 cup of strawberries in each batch
No he would get back $4.56. Start with $20 -13.59-1.85=4.56
F(-1)= -3 is (-1,-3) and f(2) = 6 is (2,6) where f(x) = y
y=mx + b is the slope-intercept form whereas m equals the slope (rate of change) and b equals the y-intercept (initial amount/what y is when x is 0.)
First, we need to find the slope between the two points (-1,-3) and (2,6). To find the slope we could use one of it's formulas
![\frac{y^2 - y^1}{x^2 - x^1}](https://tex.z-dn.net/?f=%20%5Cfrac%7By%5E2%20-%20y%5E1%7D%7Bx%5E2%20-%20x%5E1%7D%20)
.
1. (-1,-3)
2. (2,6)
![\frac{6 - -3}{2 - -1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%20-%20-3%7D%7B2%20-%20-1%7D%20)
→
![\frac{9}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%7D%7B3%7D%20)
→
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
The slope is 3 (
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
). Thusly, y = 3x + b
To find out the y-intercept, we can reverse the slope. [Note: This
![\frac{3}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B1%7D%20)
is in
![\frac{rise}{run}](https://tex.z-dn.net/?f=%20%5Cfrac%7Brise%7D%7Brun%7D%20)
where rise is 'y' and run is 'x'. Reversed would be
![\frac{-3}{-1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3%7D%7B-1%7D%20)
]. Take the second ordered pair and use our reversed slope on it until we get 0 for x.
(2, 6) ⇒ (2 - 1, 6 -3) ⇒ (1, 3) ⇒ (0,0)
Y-intercept is 0. Therefore,
y= 3x + 0 [NOTE: y = f(x), so if you want it in function notation form it's just f(x) = 3x + 0.]
Alrighty
remember
![log_a(b)=c](https://tex.z-dn.net/?f=log_a%28b%29%3Dc)
means
![a^c=b](https://tex.z-dn.net/?f=a%5Ec%3Db)
and
![ln(x)=log_e(x)](https://tex.z-dn.net/?f=ln%28x%29%3Dlog_e%28x%29)
and
![x^0=1](https://tex.z-dn.net/?f=x%5E0%3D1)
for all real values of x
so
![ln(x^2+4x-5)=0](https://tex.z-dn.net/?f=ln%28x%5E2%2B4x-5%29%3D0)
means
![log_e(x^2+4x-5)=0](https://tex.z-dn.net/?f=log_e%28x%5E2%2B4x-5%29%3D0)
means
![e^0=x^2+4x-5](https://tex.z-dn.net/?f=e%5E0%3Dx%5E2%2B4x-5)
which simplifies to
1=x²+4x-5
minus 1 both sides
0=x²+4x-6
use quadratic formula or complete the square
![x=-2+\sqrt{10}](https://tex.z-dn.net/?f=x%3D-2%2B%5Csqrt%7B10%7D)
and
![x=-2-\sqrt{10}](https://tex.z-dn.net/?f=x%3D-2-%5Csqrt%7B10%7D)
2 solutions